Delayed interval delivery in a quadruplet pregnancy: a case report and literature review - Yanan Li; Ran Chu; Yarong Li; Meiling Zhang; Yuyan Ma (BMC, 2023)
Abstract Background As the rate of multiple pregnancies increases, delayed interval delivery (DID) is increasingly being implemented to improve perinatal outcomes. But there are no international guidelines for DID in multiple pregnancies. We report a case of DID in a quadruplet pregnancy and review the relevant literature to summarize the management of DID in multiple pregnancies. Case presentation A 22-year-old woman, 22 2/7 weeks' gestation, with quadruplets, was admitted to the hospital for a first cervical cerclage due to cervical dilation. Twenty-five days later, it was found that the cervix was dilated again, so after removing the cervical cerclage, the first quadruplet was delivered vaginally (25 6/7 weeks), and a second cervical cerclage was performed. Four days later, due to re-dilation of the cervix, after removal of the cervical cerclage, the second quadruplet was delivered vaginally (26 3/7 weeks), followed by a third cervical cerclage. Six days later, the pregnancy was terminated by cesarean section due to fetal distress, and the third and fourth quadruplets were delivered (27 2/7 weeks). The patient had no postoperative complications, and all four infants were treated in the neonatal intensive care unit and discharged successfully. Conclusion This case emphasizes that comprehensive management of delayed interval delivery can improve perinatal outcomes in multiple pregnancies, including anti-infection, tocolytic therapy, practice to promote fetal lung, and cervical cerclage.